Air quality-related human health damages of wild capture seafood production in the United States - Madisen L Gittlin; Sumil K Thakrar; Madeline G Faubion; Jason D Hill (Environmental Research: Food Systems)
Exposure to air pollution is the greatest environmental health risk factor for mortality in the United States and globally, to which food production is a major contributor. Recent studies have estimated the human health impacts of air pollution from terrestrial livestock and crop production, but those of seafood production, which is an important component of many diets, are largely unknown. Here, we estimate the air quality-related human health damages of wild capture fisheries production in the United States via the emission and formation of particulate matter (PM _2.5 ). We quantify annual deaths attributable to primary and secondary PM _2.5 from commercial marine vessel emissions using county- and species-specific fishing activity and landings data. We find that, on average, wild caught seafood production is a low air quality-related health impact source of protein, with mortality health impacts 58× less than chicken, 321× less than pork, and 484× less than beef per gram of protein. The air quality-related health impacts of seafood vary widely by species and by fishing activity location. Notably, the highest impact seafood-based sources of protein production tend to be far less damaging than terrestrial animal-based sources of protein and are comparable to plant-based proteins, largely mirroring previously described broader trends for the life cycle greenhouse gas emissions of these various protein sources. Our work suggests that as global protein demand rises, shifting diets towards increased seafood consumption to meet nutritional protein requirements may offer potentially large reductions in environmentally driven harm to human health relative to terrestrial animal-based proteins.